THE IMPLEMENTATION OF COMMUNITY BASED TOURISM (CBT) IN SAMALONA ISLAND, MAKASSAR - Sitti Alya Azzahra (Politeknik Pariwisata Makassar, 2025)
This study aims to analyze the level of community involvement on Samalona Island in the management and development of Community-Based Tourism (CBT), encompassing aspects of participation from planning to implementation of tourism activities. Furthermore, this study also aims to identify tourist perceptions of service quality, attractions, and the active role of local communities in supporting tourism management on Samalona Island. The research method used a qualitative approach through direct interviews with tourism managers and tourists, as well as field observations.The research results show that the Samalona Island community is directly involved in various aspects of tourism, such as providing homestays, boat transportation services, marine tourism packages, and additional activities like banana boat rides and beach cleanliness. This involvement demonstrates a spirit of mutual cooperation, although challenges remain, particularly in the management of waste, which is not well-organized due to minimal government support. Other obstacles faced by the community include damage to facilities due to the rainy season and limited formal training to improve service capacity. Nevertheless, the community continues to strive to maintain the sustainability of tourism through simple initiatives such as beach cleanups and collaboration with students conducting environmental conservation programs. This role demonstrates that the community is not only a service provider, but also a key driver in maintaining tourist attractions. From a tourist perspective, perceptions of Samalona Island are quite positive. Tourists consider the services provided by the community adequate, marine tourism attractions such as snorkeling, diving, and the beauty of the beaches very attractive, and the friendly attitude of the community adds value to the travel experience. Tourists also see the role of the local community as crucial in improving the quality of visits and creating an authentic tourism atmosphere. This study concludes that the implementation of CBT on Samalona Island has been quite successful because the community is the main actor in tourism management. However, sustainable tourism development requires further support, particularly in terms of environmental management, community capacity building, active government involvement, and more targeted tourism promotion strategies to attract domestic and international tourists.